论粤讴的发展与演变 = An investigation of the origin and development of Yue Ou - 李威钢 Lee, Chen Kang (2010)
粤讴是19世纪流行于中国广东地区的民间文学，本文尝试理清它的起源与发展。通过对其唱词结构和内容两方面的分析，探讨粤讴的口传渊源、生产语境以及社会功能。另外，本文将粤讴发展分为前后二阶段，以比较的方式说明这种民间文学从19世纪至20世纪初百年间的演变.This thesis investigates the origin and development of Yue Ou, a type of folk literature prevailed in Canton province, China during the 19th century. Through analyzing the stylistic features and contents of some selected Yue Ou works, this paper discusses the oral conventions, social contexts and the significance of this genre of oral literature. Furthermore, by comparing Yue Ou works in different periods, this paper also discusses the changes in style and content of Yue Ou from the 19th century to the 20th century.